Dampak Penerbitan Obligasi Pemerintah - Parulian, Friska (Jurnal Ekonomi dan Pembangunan Indonesia, 2002)
This paper is written in order to explain all about the act of issuing government bonds in Indonesia_ It starts with the background, which was the collapse of many banks, then, the consequences of this act. The huge number of these bonds relative to all variables in economy such as MI, M2, and also GDP will make some problems in the future. It will burden the budget by worsening the deficit and also influence the allocation. Furthermore, it has crowding out effect to the private sector. Another big problem is how to market these bonds. Facing the condition of capital market that still underdeveloped, it will be difficult to sale the bonds. At the last part of this paper, some suggestions that can be implemented in order to solve some of the problems are offered, especially-about the development of the capital market.